Influência da condição de hipoinsulinemia-hiperglicemia na candidíase experimental sistêmica: avalição da atividade macrofágica e da distribuição das subpopulações de monóciotos sanguíneos - Venturini, James [UNESP] (2013)
Diabetis mellitus (DM) is an important predisposing factor for the development of infections, including candidiasis. Although the incidence and severity of infectious diseases in diabetic patients are related to dysfunction in the immune function, the mechanisms involved in the high susceptibility to this fungal infection are not clear. In the present study, we evaluated the influence of hypoinsulinemia-hyperglycemia (HH) on plasma levels of chemokine/cytokines, macrophage activity and distribution of peripheral blood granulocytes and monocytes subsets in a murine model of systemic candidiasis. C. albicans was intravenously inoculated in alloxan-induced HH mice, which were evaluated 12, 24 and 96 hours, and 7 days after infection. Colony-forming unit analysis and/or histopathological examination were performed on blood, bone-marrow, kidney, brain, liver and spleen. Peritoneal phagocytes were cultured with or without heat-killed C. albicans, and the production of hydrogen peroxide and nitric oxide were determined. The levels of TNF-α, IL-6, IL-10, IFN-γ, IL-12p70 and CCL2 were measured in the culture supernatants and also in the plasma of the mice. The distribution of peripheral blood granulocytes and monocytes subsets were performed by flow cytometry. Our findings showed an increased mortality in the infected HH mice, but they showed no significant differences in fungal recovery. Upon histopathological examination, no differences were observed between both infected groups, but strong discrepancies in fungal load were found among the tissues examined. High plasma levels of IL-6 and TNF-α as well as an excessive TNF-α-mediated macrophage response were also observed in the infected HH-induced mice. Soon after the fungal challenge, increased percentage of granulocytes and inflammatory monocytes was observed. C.albicans-infected HH mice presented a higher percentage of granulocytes than the non-HH ...